(untitled) (Research, Society and Development, 2022)
This study presents the proposal of a multi-criteria model to support the process of choosing applications from the perspective of educational mediation for deaf people. The proposed methodology is divided into three stages: (i) conception of the model; (ii) data collection and; (iii) classification of applications. The proposed model was applied to illustrate its operation with students listeners of the Licentiate Course in Letters/Libras at the Federal Rural University of the Semi-Árido (UFERSA) – Caraúbas Campus. The VLIBRAS and HANDTALK applications were classified as "Adequate", PRODEAF as "Poor Adequate" and FALIBRAS as "Inadequate". Thus, it is concluded that it is possible to use this multi-criteria model to select the applications that are most suitable for use in the educational mediation process of the deaf person, since it proved to be robust and effective after its application with users.